Polypeptides of the Epstein-Barr virus membrane antigen complex. - Thorley-Lawson, D A (1979)
Epstein-Barr virus (EBV)-associated membrane antigens have been purified from the plasma membranes of the producer cell line P3HR-1 NONO. The antigens were assayed with a specific rabbit anti-ebv antiserum using an 125I-labeled staphylococcal protein A binding assay. The antigens have been shown to be present on purified plasma membranes. Treatment of the plasma membranes with Triton X-100 allows the separation of two antigenically distinct classes of antigens, one soluble and one insoluble in the detergent. Immunoprecipitates of [125I5- and [35S]methionine-labeled, detergent-soluble antigens contained three major polypeptides of molecular weights of 350,000, 140,000, and 75,003 (on 7.5% sodium dodecyl sulfate-polyacrylamide gel electrophoresis) and several minor components. These polypeptides were all specifically precipitated from four EBV-producer cell lines, P3HR-1, P3HR-1 NONO, B95-8, and 7744. They could not be precipitated from producer cell lines treated with phosphonoacetic acid, which inhibits late viral functions, nor could they be precipitated from nonproducer cell lines. The 350,000 and 75,000 molecular weight polypeptides bound to Ricin and lentil lectin columns; however, most of the 140,000 molecular weight material did not. A component of molecular weight 220,000 (prominent only in P3HR-1 NONO) was probably a degradation product of the 350,000 molecular weight polypeptide.